Determination of the dispersion curve of the refractive index by the Stockwell transform - Sarac, Z.; Birkoek, H. G.; Ecevit, F. N.; Tutkun, N. (Inst Engineering Technology-Iet, 2009)
The determination of dispersion curves by the Stockwell transform (ST) is proposed. The required numerical data for dispersion curves are produced from the transmittance signal by the ST. The obtained data are then used to estimate the unknown dispersion parameters in Cauchy's formula using the genetic algorithm method through the minimisation problem based on the least-squares curve fitting. The results have shown that the dispersion curve obtained from the ST produced more improved outcomes than those obtained from the continuous wavelet transform.
Keywords: Nematic Liquid-Crystals; Optical-Constants; S-Transform; Thickness; Films; Wavelength